(untitled) (Thobaqot: Jurnal Ilmu Hadis, 2023)
Philanthropic activities have become an inseparable part of the lives of the Indonesian Islamic community. Many carry out philanthropic activities by displaying them on social media, starting from social activities such as sharing necessities, food, and so on. then the moment of giving alms was uploaded on social media. However, many of the videos of giving alms have received pros and cons from the public. This certainly contradicts the textual understanding of the hadith of giving alms in secret, but what if this understanding were linked to research that has revealed that giving alms openly would be better? Therefore, a review of the hadith on secret alms needs to be carried out comprehensively to find out the current implications of the hadith in question. As the findings of this research reveal a re-interpretation of the hadith of secret alms using Syuhudi Ismail’s analysis, there is an interpretation of the meaning of the hadith text in the words "right and left" which are said to be the meaning of a metaphor or parable, namely the words right as good, and left as bad, good it is an action or intention to eliminate bad things in favor of good things.